Reference model for the implementation of new assembly processes in the automotive sector. Issue 1 (1st January 2018) - Baraldi, Emilio C.; Kaminski, Paulo Carlos
Abstract: The literature on the planning and development of new products is of great interest to both the academic and industry communities, especially within the automotive industry. However, the same cannot be stated as easily about studies related to the implementation of new products and their processes in manufacturing, which also requires careful planning and development. For this, the purpose of this article is to present a consistent and effective reference model for the implementation of new assembly processes in the automotive sector. The model consists of a description of steps, quality checks, actions, and validations required by the product manufactured in the serial production process. The methodology has its consistency and relevance assessed by means of a practical application in the development of an automotive component assembly process, located during the final assembly. For the validation of the model, indicators of the assembly process are compared in two stages: one with the process developed by the traditional method and the other considering a process developed with the proposed method. Results show that the traditional method offer a higher rate of defective products, when compared to the presented reference model for the implementation of new assembly processes in the automotive sector. A qualitative assessment is also presented through a survey with recognized experts of the automotive environment, thus validating the proposed model.